2018
DOI: 10.2472/jsms.67.903
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption Properties of Rice Hull Charcoal for Cesium and Strontium in Aqueous Solution

Abstract: The adsorption capacity of cesium and strontium in the aqueous solution of rice hull charcoal was examined. Rice husk which was carbonized at various temperatures was added to each of cesium aqueous solution and strontium aqueous solution and stirred. As a result, rice hull charcoal carbonized at 400°C adsorbed the cesium. Rice hull charcoal carbonized at 800°C adsorbed the strontium. From this result, it was considered that the adsorption mechanism of rice hull charcoal cesium and strontium are different. Fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…At present, there are few effective utilization methods for rice husks, and various research institutes are actively conducting the research on utilization methods for rice husks. As an example, it is described that rice husk charcoal has adsorption performance for cesium (Cs) and strontium (Sr) in aqueous solution (Kobayashi et al [8]). In addition, it is reported that the rice husk ash has an adsorption ability for divalent heavy metal ions such as lead (Pb), mercury (Hg), zinc (Zn), copper (Cu), nickel (Ni) and cadmium (Cd) as shown in [9][10][11][12].…”
Section: Rice Husk Preparationmentioning
confidence: 99%
“…At present, there are few effective utilization methods for rice husks, and various research institutes are actively conducting the research on utilization methods for rice husks. As an example, it is described that rice husk charcoal has adsorption performance for cesium (Cs) and strontium (Sr) in aqueous solution (Kobayashi et al [8]). In addition, it is reported that the rice husk ash has an adsorption ability for divalent heavy metal ions such as lead (Pb), mercury (Hg), zinc (Zn), copper (Cu), nickel (Ni) and cadmium (Cd) as shown in [9][10][11][12].…”
Section: Rice Husk Preparationmentioning
confidence: 99%
“…In addition, according to the pore distribution measurements, the mesopore volume of rice hull charcoal carbonized at 400 °C were slightly increased by the alkali treatment. According to Kobayashi et al 4) , there is a correlation between the mesopore volume and the cesium and strontium adsorption amounts. Furthermore, in this study, the increase in mesopores may have improved the adsorption amount after alkali treatment.…”
Section: Cesium/strontium Adsorption Experimentsmentioning
confidence: 99%
“…Kobayashi et al reported that rice hull charcoal has adsorption capacity for cesium and strontium in aqueous solution 2 .…”
Section: Introductionmentioning
confidence: 99%